2001
DOI: 10.1097/00003226-200111000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Suture-related Complications Following Keratoplasty

Abstract: Suture-related complications frequently occur after PK. Infectious keratitis and wound separations needing surgical repair may lead to loss of best-corrected visual acuity due to scarring, induced allograft reactions, and/or increased astigmatism. Recommendations for post-PK suture management are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 13 publications
1
93
0
2
Order By: Relevance
“…Fungal infection after PKP is brought about by prolonged steroid use and the presence of sutures and donor-to-host transmission of pathogens [8,9]. Although DSAEK is considered less vulnerable to infection because it is not an opensky procedure with smaller wound size and unsutured grafts, and the period of steroid intake was limited when compared with PKP [10], donor-derived infection can still occur.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infection after PKP is brought about by prolonged steroid use and the presence of sutures and donor-to-host transmission of pathogens [8,9]. Although DSAEK is considered less vulnerable to infection because it is not an opensky procedure with smaller wound size and unsutured grafts, and the period of steroid intake was limited when compared with PKP [10], donor-derived infection can still occur.…”
Section: Discussionmentioning
confidence: 99%
“…Six immunolabeled area values, each of 47730 pixels, 2 were randomly selected per cornea sample. At least three samples per cornea were used.…”
Section: Immunohistochemistry and Immunofluorescensementioning
confidence: 99%
“…Nevertheless, sutures are considered risk factors for epithelial erosions, inflammation, suture abscess, infectious keratitis, refractive errors, and graft rejection. 2 Sutureless surgeries in ophthalmology could provide some benefits to the patient, such as shorter time of surgery, less inflammatory reaction, corneal neovascularisation, and infections. Avoiding sutures may prevent asymmetric healing, which, in turn, results in refractive aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…After penetrating keratoplasty (PKP), general guidelines for suture removal have emerged: sutures are typically removed 12 to 18 months postoperatively unless they are loose or any sign of infection is seen. 2,4 To our knowledge, no study has reported corneal infectious complications associated with corneal sutures placed during clear corneal cataract surgery. It is known that over time, nylon sutures placed during cataract surgery degrade.…”
mentioning
confidence: 99%
“…1 Previously described suture-related complications include epithelial erosions, corneal ulcers, corneal abscesses, and endophthalmitis. [2][3][4][5][6][7] However, this information is derived primarily from the corneal transplantation literature. After penetrating keratoplasty (PKP), general guidelines for suture removal have emerged: sutures are typically removed 12 to 18 months postoperatively unless they are loose or any sign of infection is seen.…”
mentioning
confidence: 99%